Same Systems, Different Outcomes - Aarts, J.; Berg, M. (Methods of Information in Medicine, 2006)
Objectives: To compare the outcome of the implementation of computerized physician order entry (CPOE) systems in two Dutch hospitals.Methods: Qualitative research methods, including interviews in both hospitals, observations of system in use, observations of staff meetings and document analysis were used to understand the implementation of CPOE. The transcribed texts and implementation documents were analyzed for relevant concepts.The transcripts and field notes were analyzed using a heuristic success and failure model with medical work as the primary focus.Results: Occasions that determined the outcome of the implementation were classified according to factors that may influence the success or failure of implementing systems.Conclusions: The themes and patterns that emerged from the data helped validate the concept of medical work as the primary focus of our analysis model; in addition the concept of a support base necessary to accept changes in medical work that result from introducing CPOE may help to understand the different implementation outcomes.
Keywords: Hospital information systems; online systems; com-puterized medical records systems; computerized physician order entry; success and failure factors; qualitative research